Fragments and dust after Holmium laser lithotripsy with or without "Moses technology": How are they different?. Issue 4 (13th December 2018) - Keller, Etienne X.; de Coninck, Vincent; Audouin, Marie; Doizi, Steeve; Bazin, Dominique; Daudon, Michel; Traxer, Olivier
Abstract : Urinary stones can be readily disintegrated by Holmium:YAG laser (Holmium laser lithotripsy), resulting in a mixture of small stone dust particles, which will spontaneously evacuate with urine and larger residual fragments (RF) requiring mechanical retrieval. Differences between fragments and dust have not been well characterized. Also, it remains unknown how the recently introduced "Moses technology" may alter stone disintegration products. Three complementary analytical techniques have been used in this study to offer an in‐depth characterization of disintegration products after in vitro Holmium laser lithotripsy: stereoscopic microscopy, scanning electron microscopy and Fourier‐transform infrared spectroscopy. Dust was separated from fragments based on its floating ability in saline irrigation. Depending on initial crystalline constituents, stone dust either conserved attributes found in larger RFs or showed changes in crystalline organization. These included conversion of calcium oxalate dihydrate towards calcium oxalate monohydrate, changes in carbapatite spectra towards an amorphous phase, changes of magnesium ammonium phosphate towards a differing amorphous and crystalline phase and the appearance of hydroxyapatite on brushite fragments. Comparatively, "Moses technology" produced more pronounced changes. These findings provide new insights suggesting a photothermal effect occurring in Holmium laser lithotripsy. Figure: Appearance of hydroxyapatite hexagons on stone dust collected after Holmium laser lithotripsy of a brushite stone using "Moses technology." Abstract : Stereoscopic microscopy, scanning electron microscopy and Fourier‐transform infrared spectroscopy are applied to better characterize disintegration products after Holmium laser lithotripsy of urinary stones. Smaller stone dust particles could be separated from larger residual fragments based on the floating ability of particles. Depending on initial crystalline constituents, stone dust revealed changes in crystalline organization; thus, suggesting a photothermal effect of Holmium laser on stones.